Groups with the same character degrees as sporadic quasisimple groups. Issue 5 (4th May 2021) - Moghadam, S. Madady; Iranmanesh, A.
Abstract: Let G be a finite group and cd ( G ) denote the set of complex irreducible character degrees of G . We prove that if H ≇ 2 . M 12 is a sporadic quasisimple group that c d ( G ) = c d ( H ), then there exists an Abelian subgroup A of G such that G is isomorphic to a central product of H and A .